Late management of traumatic complete penile amputation: A Case Report - Mustafa V Junaidi; Nasrudin Haris; Handini Annisya (Brawijaya Journal of Urology, 2024)
Traumatic complete penile amputation is a rare condition. Despite the implementation and success of known repair strategies, rural hospitals nevertheless face limitations. Furthermore, the amputation of the penis is accompanied by significant challenges and complications in the later stages. We present a case of a 43-year-old man who had previously undergone complete amputation of his penis and is now experiencing urine retention. A suprapubic cystostomy procedure was performed on the patient to divert urine. The patient planned to have a reconstructive operation by seeking treatment at a specialized tertiary referral hospital with expertise in reconstructive urology. However, the patient displayed a hesitancy to interact with healthcare practitioners. The purpose of this case report is to illustrate the complexities of traumatic total penile amputation and the early care of a rare urology case that may arise in peripheral hospitals without urologists.